Comparison Study of ALPHA 1-Antitrypsin, And Some Elements in Iraqi Cord Blood new Born with their Mothers - Wasen Hadi Saeed, Warka’a T. Al-sa’adi (Pakistan Journal of Medical & Health Sciences, 2022)
Umbilical cord blood (UCB) consider as a waste product after obstetrical but when the medicine development, it was found that UCB abundant of life saving hematopoietic stem cell and contents of soluble growth factors which is necessary for proliferation. Alpha- antitrypsin (α1-AT) is mainly synthesized in the hepatocytes by the liver then secreted to the circulation Its function is Remove the acute inflammation through supperion cytokine production and inhibits different enzymes such as neutrophil elastase (NE) in the lungs, proteinase 3, trypsin, and cathepsin G. Lead (Pb) is one of the most toxic of the heavy metals. The children especially newborns are the most affected by Pb because of they grow up rapidly resulting impaired brain and nervous system development. Cadmium (Cd) is the metal of the 20th and its effect resulted when Cd binds to proteins rich in cystein like metallothionein which causing hepatotoxicity in the liver and through circulating accumulates in the kidney tissue via and causing nephrotoxicity. Selenium (Se) as a trace element is an essential and important for human health. The vital function of Se including thyroid hormone metabolism and anti-inflammatory, immunity, activates natural killer cells, increases activated T cells proliferation, tumor cytotoxicity and antioxidant defense. The research conducted to study of 92 specimen of mothers with their new born infants in (46 normal and 46 cesarean delivery) and examined the levels of α1-AT bu enzyme liked immune assay method. Also some heavy metals i.e. Pb, Cd in addition to the Se element were determined by atomic absorption spectroscopy. The correlation between α1-AT with Pb, Cd and Se was instigated. Conclusions: The levels of α1-AT in the UCB was higher than their maternal sera after normal delivery this mean the new infant need to observation and monitoring of α1-AT level after the birth till seventh days, while α1-AT level in the UCB was lower level than their mothers sera in cesarean delivery.